Viral-Mediated Knockdown of Nucleus Accumbens Shell PAC1 Receptor Promotes Excessive Alcohol Drinking in Alcohol-Preferring Rats - Margaret A. Minnig (Frontiers Media S.A., 2021)
Alcohol use disorder (AUD) is a chronic, relapsing disorder whose genetic and environmental susceptibility components are not fully understood. Neuropeptidergic signaling has been repeatedly implicated in modulating excessive alcohol drinking, especially within sub-regions of the striatum. Here, we investigated the potential involvement of the selective receptor for pituitary adenylate cyclase-activating polypeptide (PACAP), PAC1R, in the nucleus accumbens shell (NAcc Shell) in excessive alcohol drinking in alcohol-preferring rats, an established animal model of the genetic propensity for alcoholism. Scr:sP alcohol-preferring rats were trained to operantly self-administer alcohol and then either an AAV virus short-hairpin RNA (shRNA) targeted to knockdown PAC1R, or an AAV control virus were microinfused into the NAcc Shell. NAcc Shell PAC1R shRNA knockdown virus was confirmed to significantly decrease PAC1R levels in the NAcc Shell. The effects of NAcc Shell PAC1R shRNA knockdown on ethanol self-administration were investigated using a Fixed Ratio (FR) 1 and a Progressive Ratio (PR) schedule of reinforcement. The effect of PAC1R knockdown on self-administration of an alternative reinforcer, saccharin, was also assessed. The results showed that the reduction in PAC1R in the NAcc Shell led to excessive ethanol drinking, increased preference for ethanol, and higher motivation to drink. NAcc Shell PAC1R shRNA knockdown did not comparably increase saccharin self-administration, suggesting selectivity of action. These data suggest that NAcc Shell PAC1R may serves as a “brake” on alcohol drinking, and thereby the loss of function of PAC1R leads to excessive alcohol consumption. Therefore, the PACAP/PAC1R system may represent a novel target for the treatment of AUD.